Spermatozoal, seminal plasma and blood sperm antibodies in Nigerian males (2001)
Infertility is common in Nigeria and the male role is now well recognized. Sperm antibodies (SA) have been observed as a cause of infertility and their production have in some circumstances been attributed to chronic infection of the genital tract. Sexually transmitted diseases (STDs) and infection-related infertility are reportedly highly prevalent in Nigeria. This study was therefore designed to evaluate the role of sperm antibodies and determine the involvement of STDs in the production of such SA among Nigerians. 122 adult males aged 18-56 years were investigated. 25 were normospermic, fertile males with no evidence of STDs and served as controls. 50 were infertile without STDs while 47 had proven STDs Immunobead binding technique was used for the detection of SA directly on the sperm cell, in seminal and blood plasma. Student’s t-test and anova (one-way) were used for statistical analysis of data obtained. Results showed that SA- IgG, IgA and IgM were present in blood and semen. However, mean percentage binding of these SA on motile sperm was low (<4%). Comparisons of SA in blood and semen between infertile/STDs groups and. fertile controls were not significantly different (p>0.05) The findings suggest that sperm antibodies are present but may not be associated with STDs or infertility in Nigeria males.